Wild Harvesting vs. Cultivation: Total Petasin Content in Petasites hybridus Rhizome Extracts Determines Spasmolytic Effects - Christiane Halbsguth; Verena M. Merk; Jürgen Drewe; Georg Boonen; Veronika Butterweck (Scientia Pharmaceutica)
The use of herbal medicines containing Petasites hybridus extracts has a long history in the treatment of various ailments. The observed effects are primarily due to pharmacologically active compounds such as petasin, isopetasin, and neopetasin. In evidence-based phytotherapy, extracts from leaves and rhizomes are applied for different indications. While leaf extracts are administered to treat allergic rhinitis symptoms, rhizome extracts are utilized among others in the management of gastrointestinal spasms and migraines. The quality and source of plants are critical for producing authorized herbal medicinal products. Although the preparation of P. hybridus leaf extracts from cultivated plant material is already established, the rhizomes used for preparing extracts are still derived from commercial wild collections. However, switching to cultivation is desirable to ensure consistent quality and availability. For regulatory purposes, comparative pharmacological studies are needed to assess the bioactivity of plant material from different sources. Therefore, this study analyzed rhizome extracts from wild harvesting and cultivation for their petasin composition (i.e., isopetasin, neopetasin, petasin) and spasmolytic effects on Ca2+-dependent precontracted guinea pig ileum ex vivo. The results confirm petasins as active compounds of P. hybridus rhizome extracts. Moreover, they demonstrate that the total content of petasins determines the spasmolytic effects, regardless of the individual composition of the different petasins. No significant differences in efficacy were found between cultivated and wild-collected rhizomes, demonstrating that cultivated material is a reliable, consistent, and sustainable alternative for P. hybridus rhizome extract production.